Unlocking the potential of magnetic biochar in wastewater purification: a review on the removal of bisphenol a from aqueous solution - Katibi, Kamil Kayode; Shitu, Ibrahim Garba; Md. Yunos, Khairul Faezah; Azis, Rabaah Syahidah; Iwar, Raphael Terungwa; Adamu, Suleiman Bashir; Umar, Abba Mohammed; Adebayo, Kehinde Raheef (Springer Science and Business Media Deutschland GmbH, 2024)
Bisphenol A (BPA) is an essential and extensively utilized chemical compound with significant environmental and public health risks. This review critically assesses the current water purification techniques for BPA removal, emphasizing the efficacy of adsorption technology. Within this context, we probe into the synthesis of magnetic biochar (MBC) using co-precipitation, hydrothermal carbonization, mechanical ball milling, and impregnation pyrolysis as widely applied techniques. Our analysis scrutinizes the strengths and drawbacks of these techniques, with pyrolytic temperature emerging as a critical variable influencing the physicochemical properties and performance of MBC. We explored various modification techniques including oxidation, acid and alkaline modifications, element doping, surface functional modification, nanomaterial loading, and biological alteration, to overcome the drawbacks of pristine MBC, which typically exhibits reduced adsorption performance due to its magnetic medium. These modifications enhance the physicochemical properties of MBC, enabling it to efficiently adsorb contaminants from water. MBC is efficient in the removal of BPA from water. Magnetite and maghemite iron oxides are commonly used in MBC production, with MBC demonstrating effective BPA removal fitting well with Freundlich and Langmuir models. Notably, the pseudo-second-order model accurately describes BPA removal kinetics. Key adsorption mechanisms include pore filling, electrostatic attraction, hydrophobic interactions, hydrogen bonding, π-π interactions, and electron transfer surface interactions. This review provides valuable insights into BPA removal from water using MBC and suggests future research directions for real-world water purification applications.